Isolasi dan Aktivitas Bakteri Selulolitik pada Limbah Diapers - Devi Siruwahni; Rasyidah Rasyidah (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
This study aims to isolate cellulolytic bacteria that have the potential to degrade cellulose by taking home-scale diaper waste samples. This research was also conducted to isolate and determine the ability of bacteria to degrade cellulose based on the Congo red test and filter paper degradation test. This research method is descriptive qualitative. Isolation of cellulolytic bacteria was carried out using selective Carboxymethyl Cellulose (CMC) media. The characterization was carried out by growing selected pure isolates on CMC media and then dropping congored drops to test their cellulolytic potential (cellulolytic potential is indicated by the appearance of a clear zone around the colony). The results showed that the results of isolating bacteria obtained 12 isolates that were able to grow and utilize cellulose as a carbon source. In the Congo red test isolate DS07 cellulolytic bacteria of the Hafnia genus had the highest cellulolytic index value of 2.5 mm. Isolate DS03 with the genus Bacillus had the highest ability to degrade cellulose on the Whatman No. filter paper test. 1 of 16.66%. Keywords: Bacteria, Diapers, Isolation, Cellulolytic